Ответы и объяснения

Лучший Ответ!
  • nomathpls
  • почетный грамотей
2013-05-14T17:50:00+04:00

4sin^{2}x-4cosx-5=0
4(1-cos^{2}x)-4cosx-5=0

4-4cos^{2}x-4cosx-5=0
-4cos^{2}x-4cosx-1=0

4cos^{2}x+4cosx+1=0. Пусть t=cosx.

4t^{2}+4t+1=0

(2t+1)^{2}=0
t=-\frac{1}{2}. Обратная замена:

cosx=-\frac{1}{2}
x=+\frac{2\pi}{3}+2\pi n и x=-\frac{2\pi}{3}+2\pi n

 

 

 

 

 

 

 

2013-05-14T17:51:58+04:00

4(1-cos^2x)-4cosx-5=0 
4-4cos^2x-4cosx-5=0
-4cos^2x-4cosx-1=0 делим на -1
4cos^2x+4cosx+1=0 это формула, сворачиваем
(2сosx+1)^2=0
2cosx+1=0
cosx=-1/2
x1=2п/3+2пn, n принадлежит Z 
х2=-2п/3+2пn,n принадлежит Z